Sparse Transfer Learning Accelerates and Enhances Certified Robustness: A Comprehensive Study - Li, Zhangheng; Chen, Tianlong; Li, Linyi; Li, Bo; Wang, Zhangyang (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Certified robustness is a critical measure for assessing the reliability of machine learning systems. Traditionally, the computational burden associated with certifying the robustness of machine learning models has posed a substantial challenge, particularly with the continuous expansion of model sizes. In this paper, we introduce an innovative approach to expedite the verification process for L2-norm certified robustness through sparse transfer learning. Our approach is both efficient and effective. It leverages verification results obtained from pre-training tasks and applies sparse updates to these results. To enhance performance, we incorporate dynamic sparse mask selection and introduce a novel stability-based regularizer called DiffStab. Empirical results demonstrate that our method accelerates the verification process for downstream tasks by as much as 70-80%, with only slight reductions in certified accuracy compared to dense parameter updates. We further validate that this performance improvement is even more pronounced in the few-shot transfer learning scenario.